If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -1) + (3x + 1) + (x + 4) = 12 Reorder the terms: (-1 + 4x) + (3x + 1) + (x + 4) = 12 Remove parenthesis around (-1 + 4x) -1 + 4x + (3x + 1) + (x + 4) = 12 Reorder the terms: -1 + 4x + (1 + 3x) + (x + 4) = 12 Remove parenthesis around (1 + 3x) -1 + 4x + 1 + 3x + (x + 4) = 12 Reorder the terms: -1 + 4x + 1 + 3x + (4 + x) = 12 Remove parenthesis around (4 + x) -1 + 4x + 1 + 3x + 4 + x = 12 Reorder the terms: -1 + 1 + 4 + 4x + 3x + x = 12 Combine like terms: -1 + 1 = 0 0 + 4 + 4x + 3x + x = 12 4 + 4x + 3x + x = 12 Combine like terms: 4x + 3x = 7x 4 + 7x + x = 12 Combine like terms: 7x + x = 8x 4 + 8x = 12 Solving 4 + 8x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 8x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 8x = 12 + -4 8x = 12 + -4 Combine like terms: 12 + -4 = 8 8x = 8 Divide each side by '8'. x = 1 Simplifying x = 1
| 8s-1=3(6-2s) | | -2y+10=-2(2y+1) | | 4(x-6)-6=-30 | | 6u+39=-7u | | 6+n/9=8 | | 4n+7=2n+8 | | x+(32+x)=46 | | 1/4*-20 | | 4x^2+4y^2-20x+80y=0 | | 3p+5+9-2p= | | (6+15x+36y)/9 | | 9x=14x-10 | | X+2/10=4/5+x-8/3 | | 3w-17=14 | | z-7=1-2z | | 12-2m=28 | | x^2+9x+(81/4)=0 | | 4.3x=-8.6 | | 18-45=4(x-2)-3 | | 3(x-4)=2x+6 | | 5y-x/2=8 | | -111=-3z | | 3r-(2r+1)=2 | | x^2-70x+20100=0 | | 10u-3u=14 | | x^2-70x+21300=0 | | -15t=90 | | 18x-14=15x-10 | | x+5=7-x | | P=5h+5w | | Y+-12=-10 | | 8k+7=7k-12+k |